The Effect of Giving Feedback to Students Writing - Mochamad Zainuddin (TEFLIN, 2004)
Although writing is as important as other skills such as listening, speaking, and reading, it needs more special attention. In order to write well, students need a long process to learn to write and they need continous feedback. The aim of this article is to know whether giving feedback to students writing has a significant effect or not. Two groups of students, experimental and control, were involved. The compositions of the first group were given feedback, while those of the second group were not given feedback. The study shows that provision of feedback improves students writing. In light of the result of the study, it is recommended that teachers provide feedback on students writing.